1996
DOI: 10.1111/j.1469-7998.1996.tb05445.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and quantitative study of the cloacal glands of Triturus marmoratus marmoratus (Amphibia: Salamandridae)

Abstract: With 2 plates and 1 figure in the text)The cloacal glands of the male marbled newt Triturus marmoiarus marmoratus were studied during winter and summer by histochemical and quantitative histologic methods. Four types of glands were distinguished: pelvic, dorsal, ventral, and Kingsbury's glands. The pelvic and dorsal glands have an eosinophilic epithelium and secrete neutral mucins. The ventral and Kingsbury's glands have a basophilic epithelium and secrete acid mucins. The lectin-histochemical characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…In these glands, seasonal differences have been observed. In the reproductive period, the total glandular volume and the diameter of the tubular lumen increase significantly, although the epithelial height does not show differences during the reproductive cycle (Romo et al, 1996).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In these glands, seasonal differences have been observed. In the reproductive period, the total glandular volume and the diameter of the tubular lumen increase significantly, although the epithelial height does not show differences during the reproductive cycle (Romo et al, 1996).…”
Section: Introductionmentioning
confidence: 91%
“…A preliminary lectin histochemistry study (at light microscopy level) demonstrated very poor affinity for any lectin examined in the ventral glands of T. marmoratus (Romo et al, 1996). In this study, we attempted the ultrastructural characterization of the ventral glands of Triturus marmoratus marmoratus by conventional methods and by lectin cytochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations